BOOK REVIEW: Marius Turda, „Eugenism şi modernitate. Naţiune, rasă şi biopolitică în Europa (1870-1950)” [“Eugenicism and Modernity. Nation, Race and Biopolitics in Europe (1870-1950)”], Iaşi, Polirom, 2014, 152 p., ISBN: 978-973-46-4886-3 - DĂLĂLĂU, Andrei (Studia Universitatis Babeș-Bolyai Historia, 2018)
Marius Turda's book, Eugenicism and Modernity: Nation, Race and Biopolitics in Europe (1870-1950) appeared in Romanian edition at Polirom Publishing House in 2014 under the translation of Răzvan Pârâianu from the original version, published in 2010, in English at Palgrave Publishing House Macmillan. Professor of Biomedicine History at Oxford Brookes University in the United Kingdom, Marius Turda is a specialist in the research of the history of eugenics, racism and nationalist ideologies in Central and South Eastern Europe, contributing through his works and through the exhibitions on Science and Ethnicity in drawing guidelines on European eugenics with an explicit teaching purpose: to educate the general public and the younger generation about the history of anthropology, seen as the aureolary way to complete the social image of the interwar period. The present book is divided into five chapters, which contain, in turn, four to five subchapters: Scientific ethos, War: the only eugenist of the world, Eugenic technologies of national perfection, Biopolitics and racism, Conclusions. With an Introduction built to familiarize the reader with the overall plan of the work, the first impression of the beginning pages strengthens the interdisciplinary character of the book and the subject itself: born from the fusion of pragmatism and the philosophical idealism of both precise and human sciences, eugenic studies are shaped as an identity philosophy with biological-medical foundations, to which are added literary, historical, sociological, anthropological and religious contents.